Surgical management of complicated colorectal tumors - كنعان, سمير; أيوب, عماد; عدرة, أحمد (Latakia University Journal -Medical Sciences Series, 2021)
Introduction: Mixed colorectal tumors with obstruction, perforation or hemorrhage constitute a significant proportion of all colorectal tumors, and are associated with relatively high rates of surgical complications and mortality, and this is related to the methods of surgical management used. Objective The cases of colorectal tumors pretending to be emergency are mostly poor-studied cases, with undetermined stage, which makes us in front of a rapid intervention on a relatively vague tumor, which increases the proportion of complications, prolongs hospitalization and raises death rates compared to programmed cases. The percentage of colon and rectal tumors that manifest emergency ranges between 14 - 33% of all colon tumors, and varies between different parts of the colon. Delayed diagnosis may be a direct reason for the patient to lose his opportunity to obtain a curative treatment, and this puts us in front of an urgent need to develop survey and study programs to reach an early diagnosis. The aim of the research is to study the surgical management of patients with mixed colorectal tumors and the follow-up after surgery Materials and Methods: A retrospective study was conducted that included 54 patients who attended Tishreen University Hospital on an emergency basis between 2018-2019 due to one of the complications of colorectal tumors (obstruction - perforation - hemorrhage). They were studied according to gender, age, symptoms and signs, laboratory analyzes, radiological investigations, tumor site The type of tumor complication caused by the tumor, the surgical procedure performed, the complications of the surgery and the follow-up of the patient. The results of the study were then compared with a group of international studies. Results: The study sample included 54 patients (30 males - 24 females). The average age of infection was 61 years, and the peak incidence was in the sixth and seventh decades of life. Abdominal pain was the most important clinical symptom and the most frequent by 85%, while flatulence was the most important clinical sign and appeared in 55% of patients. Leukocytosis was the most important laboratory abnormality in 55% of patients. As for the radiographic investigations, the CT scan achieved a positive rate of 87%, and the plain radiograph achieved a positive rate of 82%, while the positive echo was 80%, and the lower gastrointestinal endoscopy was 75%. The sigmoid colon was the most common site of tumor localization in our study patients, at 35%. Obstruction was the most frequent complication with 66.5%. The sigmoid colon was the most prone to obstruction with a percentage of 38.8%, and the cecum was the most prone to perforation by 50%, and all bleeding cases were caused by a tumor in the rectum and the sigmoid-rectal junction. Hartmann's procedure was the most followed procedure with 41%. The percentage of wound infection was 20.3%, intra-abdominal abscesses were 3.7%, anastomosis leakage was 7.4%, and stoma complications were 9.2%. The mortality rate was 9.3%. Conclusions: The Hartmann procedure is the least complication and the safest, so one should not hesitate to perform it when the reliability of the anastomosis is suspected or the patient's general condition is poor.